Penyuluhan Tentang Budidaya Tanaman Cabai di Luar Musim di Lahan Kering Desa Gumantar Kabupaten Lombok Utara - I Komang Damar Jaya; Bambang Budi Santoso; Jayaputra Jayaputra (Jurnal Gema Ngabdi, 2022)
Gumantar Village, Kayangan District in North Lombok Regency, has a reasonably large area of ​​dry sandy land. This dryland has the potential to be developed as a cayenne pepper-producing area in the off-season (rainy season) because the possibility of waterlogging is very low. However, very few farmers grow cayenne pepper outside of the season in Gumantar Village, and the failure rate due to pests and diseases is very high. This extension aimed to motivate farmers to grow cayenne pepper out of season by providing knowledge on cultivation procedures and techniques for managing plant pests and diseases. The method used was by meeting, discussion, and plot demonstration. Evaluation activities were carried out using two methods, namely ex-ante and summative. Overall, it can be said that the extension activities had a positive impact on the participants, as indicated by the high motivation of farmers to grow cayenne pepper out of season. Participants' satisfaction with the presented materials, along with the visualization results of the demonstration plot, were the main keys to the success of the extension.